2011
DOI: 10.1261/rna.2714411
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in expression of small, noncoding RNAs, including microRNAs, in C. elegans

Abstract: Small, noncoding RNAs (sncRNAs), including microRNAs (miRNAs), impact diverse biological events through the control of gene expression and genome stability. However, the role of these sncRNAs in aging remains largely unknown. To understand the contribution of sncRNAs to the aging process, we performed small RNA profiling by deep-sequencing over the course of Caenorhabditis elegans (C. elegans) aging. Many small RNAs, including a significant number of miRNAs, change their expression during aging in C. elegans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
156
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 72 publications
12
156
0
9
Order By: Relevance
“…Plasmid-encoded enzymes, the colicins, are involved in the cleavage of the anticodons of specific tRNAs in E. coli (36,43), resulting in the production of tRNA fragments. Similarly, it is reported that tRNA cleavage is a response to stresses in the Eukaryota (15,56), and cancer-or ageassociated changes in fragmented tRNAs have been observed (27,32). Recently, rRNA fragmentation has become another topic of interest (16,39), although the functions of fragmented rRNAs remain unclear.…”
mentioning
confidence: 98%
“…Plasmid-encoded enzymes, the colicins, are involved in the cleavage of the anticodons of specific tRNAs in E. coli (36,43), resulting in the production of tRNA fragments. Similarly, it is reported that tRNA cleavage is a response to stresses in the Eukaryota (15,56), and cancer-or ageassociated changes in fragmented tRNAs have been observed (27,32). Recently, rRNA fragmentation has become another topic of interest (16,39), although the functions of fragmented rRNAs remain unclear.…”
mentioning
confidence: 98%
“…By now, functional analyses have identified some miRNAs, such as lin-4 in C. elegans (Boehm and Slack 2005;Kenyon 2010; Smith-Vikos and Slack 2012) and miR-34 in Drosophila (Liu et al 2012), as miRNAs with critical roles in organismal and brain aging, respectively. Although most studies have focused on changes in the abundance of miRNAs with age (Ibanez-Ventoso et al 2006;de Lencastre et al 2010;Kato et al 2011), evidence suggests that miRNAs also show heterogeneity in length and sequence in different cell types and biological contexts (Burroughs et al 2010;Marti et al 2010;Li et al 2012;Westholm et al 2012;Llorens et al 2013). Such heterogeneity is mediated by imprecise Drosha and Dicer cleavages (Calabrese et al 2007;Azuma-Mukai et al 2008;Wyman et al 2011), 39 end adenylation/ uridylation (Ruby et al 2006;Landgraf et al 2007;Burroughs et al 2010;Wyman et al 2011), and RNAediting events (Kawahara et al 2007;Nishikura 2010;Alon et al 2012;Ekdahl et al 2012).…”
mentioning
confidence: 99%
“…This complex inhibits the initiation of translation by recruiting the general translation initiation factors eIF4E/G/A from capped mRNAs or eIF4G/A from uncapped mRNAs (Figure 4 A) (72) . In addition to oxidative stress, amino-acid-starvation-induced, age-associated, or tissue-specific tRNA fragmentation has also been observed in many eukaryotic cells (63,73,74) ; however, its biological roles are still unclear.…”
Section: A New Class Of Regulatory Small Rnas Derived From Trnamentioning
confidence: 99%